Safety and efficacy of cerebral embolic protection devices for patients undergoing transcatheter aortic valve replacement: An updated meta‐analysis - Dhan Bahadur Shrestha; Jurgen Shtembari; Sandesh Lamichhane; Abinash Baniya; Manoj Shahi; Swati Dhungel; Kailash Pant; Nadia R. Sutton; Pedro Villablanca; Sudhir Mungee (Health Science Reports, 2023)
Abstract Background and Aims Cerebral embolic protection (CEP) devices are employed to capture embolic debris and reduce the risk of stroke during transcatheter aortic valve replacement (TAVR). Evidence is mixed regarding the safety and efficacy of CEP. We aimed to summarize the safety and effectiveness of CEP use during TAVR. Methods Electronic databases, including PubMed, PubMed Central, Scopus, Cochrane Library, and Embase, were searched using relevant search terms for articles relating to CEP. All relevant data from 20 studies were extracted into a standardized form. Statistical analyses were performed using Revman 5.4. Odds ratio (OR) or mean differences (MDs) were used to estimate the desired outcome with a 95% confidence interval (CI). Results Twenty studies (eight randomized controlled trials [RCTs]) involving 210,871 patients (19,261 in the CEP group and 191,610 in TAVR without the CEP group) were included. The use of CEP was associated with a lower odds of 30‐day mortality by 39% (OR: 0.61, 95% CI: 0.53–0.70) and stroke by 31% (OR: 0.69, 95% CI: 0.52–0.92). Comparing devices, benefit in terms of mortality and stroke was observed with the use of the Sentinel device (Boston Scientific), but not among other devices. No differences were observed in the outcomes of acute kidney injury, major or life‐threatening bleeding events, or major vascular complications between groups. When only RCTs were included, there were no observed differences in the primary or secondary outcomes for CEP versus no CEP use during TAVR. Conclusions The totality of evidence suggests a net benefit for the use of CEP, weighted by studies in which the Sentinal device was used. However, given the RCT subanalysis, additional evidence is needed to identify patients at the highest risk of stroke for optimal decision‐making.